ALLOSTATIC NEUROPLASTICITY AND EPIGENETIC MECHANISMS IN PERSONALITY DEVELOPMENT - Oprea-Valentin BUȘU; Elena Cristina ANDREI; Mihai-Narcis POPESCU (Universitaria Publishing House, Craiova, 2020)
Genetics is part of the life of every individual having a great influence not only in terms of the transmission of physical characteristics, but also in terms of the development of the human being. Genetics makes its mark on the character and lifestyle and relationship of an individual with the social environment. Epigenetics is a relatively new field of genetics that aims to elucidate the causes of the presence or absence of a pathology caused by the activation of genes. Epigenetics does not end its activity in intrauterine life, but is in a permanent dynamic. This dynamic is influenced by the individual's lifestyle and environmental factors. Thus, by adopting sanogenic practices to maintain good systemic and mental health, as well as ensuring an environment free from pollution, an optimal state of health of the human body can be obtained. An individual's adequate state of health encompasses three major factors: physical, mental, and social health. Alteration of one factor leads to the cancellation of the other two. Therefore, in order to maintain a balance, a good functionality of the bio-psycho-social complex is necessary. The novelty element brought by epigenetics compared to classical genetics is represented by the way in which certain factors act on human DNA and produce changes throughout life.